ISLAMIC JURISPRUDENCE PERSPECTIVE IN THE PRACTICE OF DIVORCE DUE TO TAKLIK TALAK - Mohammad Fauzan Ni'ami (Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan., 2022)
Apart from being regulated in Islamic law, the concept of taklik talak is also a law regulated in Islamic jurisprudence called fiqh in Indonesia. Taklik talak is a kind of pledge / statement which shows that the husband depends on the existence of divorce from his wife, so if one or all of what has been pledged occurs, the wife can complain to the Religious Court and become the reason for divorce. If the reason is proven, the judge will decide the marriage. Regarding taklik talak in Islamic jurisprudence, it is regulated in Chapter IV of the marriage agreement and in the Regulation of the Minister of Religion No. 2 of 1990 is regulated in the marriage examination. So the research is motivated by the wrong paradigm of divorce that occurs on the basis of the husband violating the taklik talak. With the main issue of the position of divorce on the basis of taklik talak violation in the compilation of Islamic law, what is the paradigm of divorce on the basis of taklik talak violation, and analysis of divorce law on the basis of taklik talak violation according to Islamic jurisprudence.